2001
DOI: 10.1111/j.1651-2227.2001.tb00305.x
|View full text |Cite
|
Sign up to set email alerts
|

Smoking related to plasma leptin concentration in pregnant women and their newborn infants

Abstract: Leptin, a hormone produced in adipose tissue and placenta, is potentially important in relation to energy metabolism and growth. We investigated the effect of cigarette smoking on maternal plasma leptin concentration during pregnancy, and on plasma leptin concentration and weight among infants up to 13 wk of age. Plasma leptin concentration was measured in women in week 18 (n= 203) and week 35 (n=164) of pregnancy, while cotinine (nicotine metabolite) was measured in plasma sampled from mothers in week 35 of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Maternal smoking throughout pregnancy may be associated with lower cord blood leptin 77,78 though other studies have not suggested an association. 79,80 Investigations of other possible mediators, including growth hormone and IGF-1, have not been as well studied, 80 and no data exist regarding levels of any of these hormones beyond the newborn period.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal smoking throughout pregnancy may be associated with lower cord blood leptin 77,78 though other studies have not suggested an association. 79,80 Investigations of other possible mediators, including growth hormone and IGF-1, have not been as well studied, 80 and no data exist regarding levels of any of these hormones beyond the newborn period.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, tobacco smoke constituents may act on various hormonal systems that change metabolic programming 40,41 . There has also been some suggestion that prenatal tobacco smoke exposure may alter infant appetite and leptin concentrations 42–44 …”
Section: Discussionmentioning
confidence: 99%
“…Although inconsistent, there are some reports that smokers have increased blood leptin levels (Eliasson and Smith, 1999;Nicklas et al, 1999) and that chronic nicotine results in higher leptin serum concentrations in adult and prenatal animal models (Arai et al, 2001;Grove et al, 2001), which could be a mechanism for nicotine's anorexic effects. However, others have found no correlation between nicotine consumption, blood leptin levels, and decreased body weight in adult models or in mothers who smoked, questioning the significance of leptin in explaining nicotine's anorexic actions (Helland et al, 2001;Sanigorski et al, 2002).…”
Section: Leptin Does Not Regulate Body Weight In Neonatesmentioning
confidence: 97%